Association of the systemic inflammation and anthropometric measurements with cancer risk: a prospective study in MJ cohort - Bian, Zilong; Xu, Luopiao; Wang, Yuting; Tsai, Min-Kuang; Chu, David Ta-Wei; Tu, Huakang; Wen, Chi-Pang; Wu, Xifeng (Frontiers in Oncology, 2024)
ObjectiveTo investigate the specific role of inflammation in the connection between obesity and the overall incidence of cancer.MethodsA total of 356,554 participants in MJ cohort study were included. Systemic inflammation markers from blood samples and anthropometric measurements were determined using professional instruments. The Cox model was adopted to evaluate the association.ResultsOver a median follow-up of 8.2 years, 9,048 cancer cases were identified. For individual systemic inflammation biomarkers, the overall cancer risk significantly escalated as blood C-reactive protein (CRP) (hazard ratio (HR)=1.036 (1.017-1.054)) and globulin (GLO) (HR=1.128 (1.105-1.152)) levels increased, and as hemoglobin (HEMO) (HR=0.863 (0.842-0.884)), albumin (ALB) (HR=0.846 (0.829-0.863)) and platelets (PLA) (HR=0.842 (0.827-0.858)) levels decreased. For composite indicators, most of them existed a significant relationship to the overall cancer risk. Most indicators were correlated with the overall cancer and obesity-related cancer risk, but there was a reduction of association with non-obesity related cancer risk. Most of indicators mediated the association between anthropometric measurements and overall cancer risk.ConclusionsSystemic inflammatory state was significantly associated with increased risks of cancer risk. Inflammation biomarkers were found to partly mediate the association between obesity and cancer risk.